A Comparative Analysis of Patient Service Efficiency Using Electronic Medical Records and Conventional Medical Records at Dr. Harjono S. Ponorogo Regional General Hospital - Gilby Firsta Wahyu Saputra; Ria Fajar Nurhastuti (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2025)
Medical records are a crucial component in hospital health services. With technological advancement, Electronic Medical Records (EMR) are expected to improve service efficiency. This study aims to identify and compare the efficiency of patient services using EMR and Conventional Medical Records (CMR) at RSUD Dr. Harjono S. Ponorogo. This research employed a qualitative comparative method with data collected through observation and interviews. The study involved five informants: a doctor, a nurse, a conventional medical record officer, an electronic medical record officer, and an IT staff member involved in medical record management. The results show that EMR is more efficient in terms of time, cost, data security, information access, and reporting. CMR still holds advantages in direct physical access without relying on technology. It is concluded that EMR implementation supports faster and more integrated patient services. Therefore, hospitals are encouraged to adopt EMR systems comprehensively.